Evolution of inverter ground impedances for PV modules with various backsheet types - Buerhop, Claudia; Stroyuk, Oleksandr; Pickel, Tobias; Hauch, Jens; Peters, Ian Marius (Progress in Photovoltaics, 2022)
Herein, we present results that emphasize the importance of retaining high insulation resistance in polymer backsheets for the reliable operation of photovoltaic installations. By correlating inverter monitoring data, meteorological data, and spectroscopic information from backsheet materials of photovoltaic modules, we derive performance and degradation rates for inverters connected to photovoltaic modules with several backsheet types. The feasibility of evaluating the degradation status of photovoltaic modules in the field through spectroscopic analysis of the water content in backsheet and encapsulant is demonstrated. We show that an increase in water content is a sign for reduced leakage resistance. Ground impedance was measured alongside relative humidity and temperature for three specific backsheet types. Inverters with polyamide and fluorinated coating/polyethylene terephthalate backsheets showed a significant drop in ground impedance at high humidity, RH > 70%. A loss rate of −2 kΩ/day in ground impedance was found for inverters connected to modules with certain fluorinated backsheets. This value is twice as high as for inverters connected to modules with polyamide backsheets. Time series show that the sensitivity to moisture and water ingress increases with time, especially for modules with polyamide and certain fluorinated backsheets. The worst degradation scenario observed had an annual yield loss of 27% due to inverter outages on humid days. About 25% of inverter trip alerts after 8 years of operation included modules with the specific fluorinated backsheet. In general, the study revealed a distinct backsheet impact on ground impedance and operation of inverters and the resulting yield showing an important role of the choice of polymers for reliable and long-lasting photovoltaic systems.
CRIS-Team Scopus Importer:2022-09-16
Keywords: degradation; ground impedance; insulation resistance; near-infrared spectroscopy